Produktive Parks entwerfen. Geschichte und aktuelle Praxis biologischer Produktion in europäischen Parks. - Timpe, Axel (My University, 2017)
Die landschaftsarchitektonische Praxis hat in den letzten zwei Dekaden zahlreiche Parks geschaffen, die land- oder forstwirtschaftliche Produktion als wichtige Flächennutzungen integrieren oder gar in den Vordergrund des Entwurfskonzeptes stellen. Dieses Phänomen ist bisher weder auf breiter empirischer Grundlage untersucht noch in die Entwicklung der Landschaftsarchitektur als Disziplin und des Parks als einem ihrer wichtigsten Objekte eingeordnet. Die Arbeit füllt diese Lücke in der Forschung, indem sie die neuen Parks unter dem Begriff Produktiver Park beschreibt und untersucht. Die Rolle des Produktiven Parks in der Geschichte der europäischen Landschaftsarchitektur wird durch Literaturauswertung dargestellt, sein Auftreten in der aktuellen Praxis in 16 Fallstudien analysiert. Diese durch zeichnerische Plananalyse, Literaturrecherche und Ortsbesuche untersuchten Parks bestätigen die neue Bedeutung der Produktion im Park. Sie lassen sich anhand ihrer wichtigsten räumlichen Komponenten (Produktionsflächen, Erschließungsnetz, raumbildende Gehölze, Parkausstattung) in verschiedene Strukturtypen einteilen. Die Verbindung der Produktion mit den anderen räumlichen Elementen folgt dabei unterschiedlichen Integrationstypen, die die vergleichende Analyse der untersuchten Parks ebenfalls präsentiert. Die Struktur- und Raumtypen bilden einen Katalog von Optionen für das Entwerfen Produktiver Parks in der Zukunft. Als wichtigstes Handlungsmodell für die Schaffung und Unterhaltung Produktiver Parks zeigt sich die Co-Produktion des Parks als ein öffentliches Gut. Diese findet in den untersuchten Parks auf verschiedenen Stufen von der Koppelproduktion über das Co-Design und die echte Co-Produktion bis hin zur Community Co-Produktion statt.

In the course of the last two decades, landscape architectural practice has created numerous parks in which agricultural or silvicultural production is integrated as an important land-use or even a central as-pect of the design concept. Until now, this phenomenon has not been investigated on a broad empirical basis. Neither has it been analysed in relation to the development of landscape architecture as a disci-pline and the park as one of its most prominent objects.The present study fills this research gap. It explores and describes this new kind of park under the name of the Productive Park. Part of the investigation is to outline the role of Productive Parks in the history of European landscape architecture based on literature search. Subsequently, the recent practice of Pro-ductive Parks is analysed on the basis of 16 case studies. The analysis focusses on four research ques-tions: The extent to which contemporary practice aligns with the historical tradition of Productive Parks; the comparison of the analysed parks in consideration of the few existing theoretical approaches to the question of how park and production may integrate; the definition of the Productive Park as a new type of park as well as the creation of a spatial typology based on empirical research; and finally, the exploration of models of action applicable to the creation and maintenance of Productive Parks.Especially the two latter research questions are sustained by two different dimensions of the term park , which can be traced back to the radicals parricus (enclosure) and parcere (save, treat with care). As a noun, parricus describes the spatial character and the physical elements of a park. The verb parcere de-scribes the actions when dealing with commons that need to be protected and developed. The comple-mentarity of these two dimensions structures the research. Finally, in the conclusions, both aspects are combined in complex design strategies. Three models of Productive Parks are described. They are meant to be a guideline and and provide inspiration for future teaching and practice in landscape architecture.From the historical view, the productive use of nature is the origin of the park. In the course of several centuries and spanning different stylistic periods, parks served as a laboratory and model for innovation in agriculture and forestry. From the 19th century onwards, the importance of this role has gradually de-creased and the park has been transformed into the urban park, a protected space for recreation oriented towards social and societal development. In recent years, the interest in production in parks is regrowing. It connects innovative models of agricultural production with new forms of common work and production.The 16 parks analysed here by means of literature research, plan analysis and site visits give evidence of the new importance of production in parks. Based on their main components (productive land, access network, space-defining plantations, equipment elements), these parks can be classified in different types of spatial structure. The connection between production in the park and other physical elements can be sorted according to the types of integration also presented in the comparative analysis of the case-study parks. The types of spatial structure and of integration can be read as a catalogue of possible design solutions for Productive Parks.Co-Production has been identified as the most important approach for the creation and maintenance of Productive parks as common good. In the parks that were analysed, co-production can be found on different levels, starting from joint production and rising to co-design and actual co-production and finally community co-production as the highest level. The study clarifies the roles of stakeholders on the different levels of co-production.The results presented here add considerable new knowledge to the state of research. Based on empirical research, the analysis demonstrates how biological production can become a special quality in hybrid park types. This leads to the identification of three principal models of Productive Parks, which them-selves encompass complex design strategies: the Productive urban Park, agrarian urban landscapes as Productive Parks and Productive post-industrial Parks. With regards to landscape architecture in general, the forms of co-production tested in Productive parks can lead to a new understanding of parks as a place and instrument of common action. The landscape architectural design serves as a tool that coordi-nates the co-production of public space.
Designing productive parks. History and current practise of bio-based production in European parks.
Keywords: Freiraumplanung; Landschaftsplanung; Landschaftsgestaltung; Park; Vegetation; Öffentlicher Raum; Stadtlandschaft; Flächennutzung; Nutzungsänderung; Bewirtschaftung; Gemeinschaftsnutzung; Fallstudie; Urban Gardening; Nahrungsmittelproduktion